Determinants of fertility experience among reproductive women age (15-49) in Ethiopia: Application of count regression models. - Bantie Getnet Yirsaw; Birhan Ambachew Taye; Wullo Sisay Seretew; Aychew Kassa Belete; Tigabu Kidie Tesfie (PLoS ONE, 2024)
Introduction Fertility refers to the average number of children born to a woman over her reproductive years. Due to cultural norms, economic development, education, access to healthcare, and government policies, fertility rates vary significantly across different countries and regions of the world. Ethiopia is one of the developing countries in Sub-Sahara Africa and its fertility rate has consistently been one of the highest in the world. Hence the main goal of this study was to identify the leading factors for the total number of children born per mother in Ethiopia. Methods This study used the most recent secondary data obtained from the 2019 Ethiopia Mini Demographic and Health Survey. A total weighted sample of 8885 women aged 15 to 49 was included in the study. The primary outcome variable in this study was the number of children born per mother, and different socio-demographic and economic factors that could influence fertility experience were included. The analysis was performed using STATA version 17 software. Negative Binomial regression model was used to assess the association between outcome and predictor variables. A p-value <0.05 was considered to be statistically significant. Results From a total of 8885 women, on average approximately 2.73 children were born per mother. Age of mothers (IRR = 1.08, 95% CI: (1.077, 1.082)), religion for Muslim (IRR = 1.13, 95% CI: (1.08, 1.18)) and others (IRR = 1.16, 95% CI: (1.11, 1.22)), level of education secondary and above (IRR = .61, 95% CI: (.58, .65)) and primary (IRR = .84, 95% CI: (.81, .87)), household member of six to nine (IRR = 1.24, 95% CI: (1.20, 1.28)) and household members more than nine people (IRR = 1.14, 95% CI: (1.07, 1.21)), wealth index for rich (IRR = .94, 95%, CI: (.91, .98)), marital status for not married (IRR = .49, 95%, CI: (.48, .51)), pregnant mothers (IRR = 1.08, 95%, CI: (1.02, 1.13)) and contraceptive users (IRR = 1.12, 95%, CI: (1.09, 1.16)) were the signficant variables for number of children ever born per mother. Conclusion In Ethiopia, the average number of children born per mother was approximately 2.73. Poisson and Negative Binomial regression models were compared, and we found the Negative Binomial regression model to be better to identify the determinants of fertility experience in Ethiopia. Age of mothers, religion, current pregnancy, use of contraceptive methods, mothers' education level, household members, wealth index, number of children aged five and under, region (Somali, Gambela, and Addis Ababa), and marital status were the determinants responsible for fertility experience among mothers in Ethiopia. These findings are helpful for policymakers and healthcare professionals for developing targeted interventions and programs aimed at improving the high fertility rate experience in Ethiopia.